ILUSTRASI, ILUSTRATOR, DAN CERPEN - FX. ruWidyatmoko (Ars: Jurnal Seni Rupa dan Desain, 2007)
According to most people, an illustration is understood as a complimentary, decorative picturewhich is used to clarify the idea o f a text as well as to support the atmosphere created front the text. This isapplied tc the illustration o f short stories published in Kompas. Even though these arc "different" from thetext, they are still based upon the text. It is clear that there is no need to investigate whether an illustration isrelated to the short story or not. The problem remains that either there is a new interpretation towards thetext as a result o f the “difference’’, or that the illustration is merely decorative, as most people believe.TJtis composition offers a different perspective in examining illustrations, especially those whichaccompany short stories in Kompas the same topic discussed by Effendi in "llustrasi dan Cerpen",published in the journal ARS, No. 04, January-April 2007 (p. 56-58). It thus provides an alternative readingo f Effendi’s ozvn composition.Keywords: illustration, illustrator, text